KEWENANGAN PENGISIAN ANGGOTA BAWASLU DI PROVINSI ACEH - T.Muhammad Nurdhia Ikhsan, Husni Jalil, Adwani. (Jurnal Ilmu Hukum, 2016)
Abstract: Article 1/ No.5/ Act No. 15/ Year 2011 on the Implementation of General Election states that "the implementation of general election at the national level is the responsibility of organizations, the so called the General Election Commission (or known as KPU in bahasa) and the General Election Controller (or the national BAWASLU in bahasa). Both of them have an integrated function in implementing the election for choosing the member of the House of Parliaments (DPR in bahasa), the Regional Representative Council (or DPD in bahasa), the House of Parliaments at regional level (or DPRD in bahasa), the President and Vice President elected directly by the people, as well as to elect governors, regents, and city-majors, democratically”. Furthermore, Article 60 (3) letter a Law Number 11/ Year 2006 regarding the Government of Aceh states that “members of the General Election Controller as being referred in paragraph (1) and paragraph (2) could be proposed by the House of Parliaments of Aceh Province (or DPRA in bahasa)/ the House of Parliaments at the District Level (or DPRK in bahasa) up to a maximum of 5 (five) person”. This may cause disharmony and may impede the election itself.  The objective of this study is to determine which institution is actually being authorized to choose the member of General Election Controller in Aceh province. Methodology applied in this research was juridical normative research (or juridical normative). Results showed that the national BAWASLU has the highest authority to choose its member at the provincial level, including in Aceh. Moreover, the Election Supervision Committee (PANWASLIH) is merely authorized to supervise election for choosing provincial leaders. This study suggests the Government of Aceh and the national BAWASLU to understand and to fulfill their responsibilities according to their authorities so that disharmony and misinterpretation can be avoided.Keywords : Government of Aceh, general election, election controller, election committee.Abstrak: Pasal 1 angka 5 UU Nomor 15 Tahun 2011 tentang Penyelenggaraan Pemilihan Umum menyatakan bahwa: "Penyelenggaraan Pemilu adalah lembaga yang menyelenggarakan Pemilu yang terdiri atas Komisi Pemilihan Umum (KPU) dan Badan Pengawas Pemilu (BAWASLU) sebagai satu kesatuan fungsi penyelenggaraan Pemilu untuk memilih anggota Dewan Perwakilan Rakyat (DPR), Dewan Perwakilan Daerah (DPD), Dewan Perwakilan Rakyat Daerah (DPRD), Presiden dan Wakil Presiden secara Langsung oleh Rakyat, serta untuk memilih Gubernur, Bupati, dan Walikota secara demokratis". Selain itu, Pasal 60 ayat (3) huruf a Undang-Undang Nomor 11 Tahun 2006 tentang Pemerintahan Aceh menyebutkan bahwa “anggota Panitia Pengawas Pemilihan sebagaimana dimaksud pada ayat (1) dan ayat (2), masing-masing sebanyak 5 (lima) orang yang diusulkan oleh DPRA/DPRK”. Hal ini dapat menyebabkan disharmonisasi aturan sehingga  dapat menghambat tahapan pemilu itu sendiri. Tujuan penelitian untuk mengetahui  lembaga mana yang sebenarnya dapat mengisi anggota BAWASLU Aceh. Metode penelitian yang digunakan  penelitian hukum normatif (yuridis normative). Hasil penelitian menunjukkan bahwa BAWASLU pusatlah yang berwenang mengisi anggota BAWASLU di tingkat provinsi, termasuk di provinsi Aceh. Selain itu, panitia pengawas pemilihan (PANWASLIH) hanya berwenang mengawasi PILKADA. Disarankan kepada pemerintah aceh dan BAWASLU pusat untuk memahami dan mengisi tanggung jawabnya sesuai kewenangan sehingga disharmonisasi dan misinterpretasi dapat dihindari. Kata kunci : Pemerintah Aceh, pemilihan umum, pengawas pemilihan, komiti pemilihan.